Seismic retrofit options for non-structural building partition walls: Impact on loss estimation and cost-benefit analysis - Sousa, Luis; Monteiro, Ricardo (Engineering structures, 2018)
•The impact of non-structural partition walls on earthquake losses is analysed.•A comprehensive review of retrofit solutions for this type of components is presented.•Life-cycle assessment and retrofit cost-benefit analyses are performed.•Six real building configurations and three different seismicity levels are assessed.•Non-structural retrofit alone may be able to achieve the return of initial investment. The importance of non-structural components in building performance under seismic action is well recognized in the scientific community. Damage to residential buildings registered in past earthquakes has demonstrated that the damage to non-structural components represents a substantial percentage to the resulting economic losses. In the context of performance-based earthquake engineering (PBEE), the probabilistic estimation of building-specific losses has highlighted the importance of non-structural walls, in particular, due to their direct influence on building response and contribution to the overall damage. However, limited research has been produced on the subject of seismic retrofit of non-structural components and their economic advantages. In this manuscript, focus is given to non-structural partition walls, with the aim of determining the potential economic benefit of implementing non-structural retrofit solutions, in terms of the corresponding reduction in average annual earthquake losses. Building on an extensive literature review on the state-of-the-art of non-structural retrofit solutions, representative retrofit options are investigated for six combinations of building class and seismic hazard at the building location (in Italy), by means of probabilistic seismic loss estimation and corresponding cost-benefit analysis. The results show that the seismic retrofit of non-structural partition walls only (as opposed to retrofitting both structural and non-structural components) can be sufficient to achieve a reduction of seismic losses that guarantees the return of the retrofit investment during the building’s life cycle, specifically when dealing with highly vulnerable buildings located in regions of high seismicity.